Building Customer Relations through CRM - A Theoretical Framework of Software Services Firms in Bangalore Cluster - Shruthi, V. K.; Devaraja, T. S. (Indian Journal of Marketing, 2011)
Worldwide, service firms have been the pioneers in adopting the practices of Customer Relationship Management (CRM). In India too, the service firms took some of the early initiatives in CRM. The CRM as a strategic management tool, has been successfully implemented in various service firms like IT, hospitality, telecom and financial services. This study explores the conceptual foundations of CRM by examining the use of CRM in Software Service Firms. The primary objective of this paper is to help in understanding the CRM practices used by Indian software service firms that have been very successful worldwide and also to understand the use of CRM to profitably manage customer relations.